2021
DOI: 10.1002/jum.15676
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Utility of Ultrasound Versus Physical Examination in Assessing Knee Effusions

Abstract: Knee effusion can be detected by physical examination, ultrasound and MRI, but the utility of each test is unclear. This study aimed to analyze the diagnostic value of physical examination and ultrasound for knee effusion. A systematic literature search of electronic databases was completed. Bivariate mixed-effects regression modelling was used to estimate sensitivity, specificity and diagnostic odds ratio of physical examination and ultrasound diagnosis of knee effusion. Sensitivity of ultrasound diagnosis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…RTMSPUS not only addresses this problem but improves upon the known limitations of the physical examination. Just as the physical examination dramatically improves the accuracy of a verbal history in confirming suspected diagnoses, so does a focused POCUS examination dramatically improve upon a physical examination [ 29 , 30 , 31 ]. Thus, the authors suggest that a self-performed ultrasound examination be considered whenever a patient is perceived to potentially benefit from an improved physical examination during a remote medical encounter.…”
Section: Terrestrial Concepts Of Remote Telementored Self-performed U...mentioning
confidence: 99%
“…RTMSPUS not only addresses this problem but improves upon the known limitations of the physical examination. Just as the physical examination dramatically improves the accuracy of a verbal history in confirming suspected diagnoses, so does a focused POCUS examination dramatically improve upon a physical examination [ 29 , 30 , 31 ]. Thus, the authors suggest that a self-performed ultrasound examination be considered whenever a patient is perceived to potentially benefit from an improved physical examination during a remote medical encounter.…”
Section: Terrestrial Concepts Of Remote Telementored Self-performed U...mentioning
confidence: 99%
“…Importantly, ultrasound cannot assess for early bony changes associated with osteomyelitis; thus, a negative study does not rule out this disease process. [13][14][15][16][17]…”
Section: Ultrasoundmentioning
confidence: 99%
“…Ultrasonography has superior sensitivity and specificity in the detection of knee effusion relative to the physical examination and is noninvasive, repeatable, and has no associated ionizing radiation. [13][14][15] Bedside ultrasound can be helpful in guiding joint aspirations, particularly in the patient with a small knee effusion. In the patient with juvenile idiopathic arthritis (JIA), ultrasound can also demonstrate signs of synovitis and associated inflammatory periarticular changes, thus assessing disease activity.…”
Section: Ultrasoundmentioning
confidence: 99%
“…Although knee effusions are commonly believed to be clinically obvious, the diagnostic accuracy of physical examination tests lack accuracy and varies with examiner experience. A recent systematic review found the bulge sign to be 33% sensitive and the patellar tap to be only 15% sensitive for knee effusion [1]. Multiple studies have demonstrated that ultrasound is superior to clinical examination in the detection and localization of a knee effusion, as the physical examination is 69% sensitive and 85% specific compared to ultrasound [1].…”
mentioning
confidence: 99%
“…A recent systematic review found the bulge sign to be 33% sensitive and the patellar tap to be only 15% sensitive for knee effusion [1]. Multiple studies have demonstrated that ultrasound is superior to clinical examination in the detection and localization of a knee effusion, as the physical examination is 69% sensitive and 85% specific compared to ultrasound [1]. When reviewing the clinical examination for septic arthritis, only joint pain, history of joint swelling, and fever were found in more than 50% of patients [2].…”
mentioning
confidence: 99%